2017
DOI: 10.1002/chem.201704281
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Electrodes Modified with DNA Duplexes Possessing a Porphyrin Dimer

Abstract: This work describes the formation of a porphyrin (Por) dimer using a DNA duplex as a scaffold and photocurrent generation from electrodes modified with a monolayer of Por-DNA conjugates. The solid-phase click reaction between an azide-porphyrin and oligonucleotide labeled with an ethynyl group on CPG support was utilized to conjugate the Por to the DNA. UV/Vis absorption and circular dichroism (CD) spectral studies revealed that the Por dimer can be formed through DNA hybridization and that through-space elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 79 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…Thiol-derivatized DNA duplexes possessing DMPyP were immobilized on the gold electrode through the formation of a AuÀ S linkage to prepare a monolayer of DNA on the surface according to a previous method. [29,46,64] DMPyP was used instead of TMPyP as the photosensitizer because DMPyP showed a specific binding at the binding site, while a nonspecific binding of TMPyP to DNA via intercalation cannot be ruled out. To minimize the effect of electron transfer quenching by the guanine nucleobases, the binding sites of DMPyP were placed in a continuous A/T sequence.…”
Section: Photoresponsive Electrodes Modified With Dna/porphyrin Compl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thiol-derivatized DNA duplexes possessing DMPyP were immobilized on the gold electrode through the formation of a AuÀ S linkage to prepare a monolayer of DNA on the surface according to a previous method. [29,46,64] DMPyP was used instead of TMPyP as the photosensitizer because DMPyP showed a specific binding at the binding site, while a nonspecific binding of TMPyP to DNA via intercalation cannot be ruled out. To minimize the effect of electron transfer quenching by the guanine nucleobases, the binding sites of DMPyP were placed in a continuous A/T sequence.…”
Section: Photoresponsive Electrodes Modified With Dna/porphyrin Compl...mentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] DNA-porphyrin conjugates have been proven to be useful as photoactive materials to control the energy transfer and electron transfer and to design a light-harvesting system for photonic applications. [30][31][32][33][34] Although there are quite a few reports of DNA conjugates with porphyrin derivatives, [22][23][24][25][26][27][28][29]35] the non-covalent approach to construct molecular complexes of DNA with porphyrin derivatives is limited. Porphyrin arrays assembled on a DNA structure [27,[36][37] or on a single-stranded DNA through hydrogen bonding interactions have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, it did not provide any bactericidal effect on Gram-negative strains even under white light irradiation. The 5-(4-azidophenyl)porphyrin P82 was also used to form porphyrin-DNA conjugates [68]. The conjugates were prepared by solid-phase click reaction between the azide P82 and oligodeoxynucleotides with an ethynyl group on controlled pore glass support (Scheme 29).…”
Section: Scheme 23mentioning
confidence: 99%
“…Boyle and co-workers also used the tricationic porphyrin P130 to produce a molecular theranostic agent suitable for use as a PET radiotracer and as a photosensitizer for PDT [85]. These authors developed a procedure to prepare 69/71 Ga and 68 Ga radiolabeled azide-functionalized porphyrins P132, and the metalated porphyrins were then bioconjugated to the alkyne-functionalized dodecapeptide TWYKIAFQRNRK 37 (Scheme 44). This peptide exhibits a good affinity for the α6β1-integrin, which is involved in cellular migration and is also upregulated in multiple cancers, including breast carcinomas and glioblastomas.…”
Section: Other Azido-substituted Porphyrinsmentioning
confidence: 99%
“…The copper‐catalyzed alkyne−azide cycloaddition (CuAAC), has been a widely used reaction for post‐synthetic labeling of oligonucleotides, both in solution phase and solid phase syntheses, because it is a highly efficient, highly regioselective, facile reaction employing mild reaction‐conditions and readily accessible starting materials. Recently our group demonstrated that a dual‐tetraphenylporphyrin consecutively labeled oligonucleotide could be prepared by the CuAAC coupling of a tetraphenylporphyrin bearing an azide group with the 5‐ethynyl uridine moieties in an oligonucleotide through a solid phase synthesis procedure …”
Section: Introductionmentioning
confidence: 99%